PROBLEMS OF PLURALISM IN MODERN INDONESIAN ISLAM (JOURNAL OF INDONESIAN ISLAM, 2014)
Different from Western Europe, in which democracy and pluralism are achieved by eliminating the role of religion in politics and public sphere, religion in Indonesia plays a positive role. However, the main stumbling block of this positive role is the faulty assumptions and suspicions among Indonesian Muslims about the concept of “the other”, be it internally among Muslims or externally with the non-Muslims. Stereotypical terms such as “extreme Islam” (terrorist Islam) and “Christian-Catholic conspiracy” have resulted in disastrous consequences in society and do not at all support positive change towards democracy and pluralism. This article discusses how pluralism is, perceived, understood and practiced in Indonesia by Muslims. The author argues that it is the responsibility of Indonesian Muslim leaders to reexamine the religious system which in essence does not support the realization of a democratic and pluralistic modern society in order to comply with the standard of international law and human rights.